(untitled) (Konferensiyalar | Conferences, 2024)
Humanitarian knowledge advancement has presented a challenge to create a new term that accurately reflects the meaning of a linguistic symbol, overcoming the constraints of traditional sense and significance, while seamlessly integrating logical-psychological and linguistic concepts.